Healthy nutrition as a disease prevention factor: WHO Policy and National Experience (to mark the 75th anniversary of WHO in Ukraine) - M.P. Gulich; O.D. Petrenko (Medičnì Perspektivi)
In the context of the constant increase in the burden of chronic non-communicable diseases, the World Health Organization's (WHO) activities are aimed at developing policies and strategies in the field of non-communicable disease (NCD) prevention, which have been continuously evolving. The work is dedicated to examining the sequential policy of the WHO outlined in documents regarding the link between nutrition and the development of non-communicable diseases. The objective of this study is to identify the main stages of WHO's policy on healthy nutrition as a key prerequisite for preventing the development of non-communicable diseases and outline the corresponding measures in Ukraine. Materials and methods: informational, bibliographic, normative-legal. The study utilized systematic-structural, formal-logical, bibliographic, and non-formalized (traditional) analysis methods. An analysis of WHO's policy on healthy nutrition as a factor in preventing the development of chronic non-communicable diseases has been conducted. The key stages of policy development and decision-making at the global level over the past three decades have been identified. It has been determined that the evolution of the role of nutrition within WHO's policy has progressed from urging governments to develop national food policies and create national action plans in the 1990s to global strategies and actions that have taken place in the 21st century. The basic WHO documents regarding the link between nutrition and the development of chronic diseases have been examined, as well as the expansion of understanding the content and necessity of healthy nutrition. The implementation of WHO's policy in Ukraine has been highlighted: the "National Action Plan on Non-communicable Diseases to Achieve the Sustainable Development Goals by 2030" (2018) has been developed and implemented, serving as a roadmap for the development of a series of guiding documents. The most important of these documents pertain to the organization and standards of healthy nutrition for children. However, the formation of a national regulatory and legal framework regarding healthy nutrition has not yet been completed. It has been determined that Ukraine needs to improve its policy on limiting the use of saturated fats, industrially produced trans fatty acids, and marketing unhealthy food and non-alcoholic beverages targeted at children. There is a need for extensive informational and educational activities to promote WHO's recommendations on healthy nutrition.